Predictors of cardiomyopathy in patients with type-2 diabetes mellitus with and without cardiovascular complications: A cross-sectional study. (August 2019) - Bashir, Aamir; Azharuddin, Md; Rashid, Ishfaq; Murti, Krishna; Pandey, Krishna
Highlights: Diabetes incidence is escalating rapidly and cardiovascular complications are predominantly coexistent. Early prediction of cardiomyopathy in T2DM will benefit clinical judgment of the disease. Different novel biomarkers available were used to assess cardiomyopathy status in study participants. BNP and calcium levels were significantly higher in diabetic hypertensive with dyslipidemia patients. Study outcomes will help to develop specified diagnostic and therapeutic strategies. Abstract: Aim: This study was aimed to evaluate the cardiomyopathy in patients with type 2 diabetes mellitus (T2DM) who live with or without cardiovascular complications by estimating different cardiac biomarkers. Methods: This cross-sectional study enrolled 125 participants including 25 healthy volunteers and 100 T2DM patients. After meeting all inclusion criteria, the participants were categorized into five groups (N = 25 in each) as; healthy volunteers (I), T2DM (II), T2DM with hypertension (III), T2DM with dyslipidemia (IV), T2DM with hypertension and dyslipidemia (V). Pearson's correlation analysis was performed to assess the significant association between cardiac biomarkers other biochemical parameters. P-values <0.05 were considered statistically significant. Results: The average age of the participants was found to be 55.04 ± 7.51 years. The positive correlation was found between HbA1c and calcium or BNP levels however, a negative association was observed with zinc level. Group V showed higher mean of BNP (pg/mL) as 86.73 ± 64.49 followed by Group III (61.02 ± 53.69), IV (33.88 ± 33.71), II (13.49 ± 11.67) and I (5.54 ± 1.49) which predicts the subclinical cardiomyopathies in the respective groups. Serum zinc (µg/dL) level were significantly lower in Group V (52.72 ± 12.16) followed by III (56.15 ± 9.64), IV (58.10 ± 10.05), II (59.49 ± 11.33) and I (73.96 ± 21.91). Conclusions: In summary, BNP and calcium levels were significantly elevated while zinc was significantly reduced in T2DM patients with cardiovascular complication. Results from the study also shown positive correlation between BNP, calcium, Troponin-I levels and blood pressure. However, further longitudinal studies required to confirm these findings.